Adolescent smoking behavior and its related factors in coastal area of Kendari, Indonesia - Lestari, Hariati; Irma; Yasnani (Public Health of Indonesia, 2023)
Background: Smoking is a behavior that does not occur spontaneously but rather evolves through a series of processes influenced by various internal and external factors. Smoking leads to a decline in health, impacting the quality of life for children in the new generation. Objective: This study aimed to analyze the relationship between the social environment, media/advertising exposure, the role of parents, and the role of teachers in adolescent smoking behavior in the coastal area of Kendari, Indonesia Methods: The study utilized a cross-sectional study approach. The population comprised all adolescents in the coastal area of Kendari, with a sample size of 526 students, including both male and female students. The study was conducted in April 2023. Data were collected through a questionnaire, and were analyzed using Chi-square test. Results: The study found that a percentage of students engaged in smoking behavior. Additionally, 100% (221 individuals) of students reported being influenced by cigarette advertising, leading to smoking. Furthermore, 92.4% of students with parents in a deficient role exhibited smoking behavior, and 83.2% of students with teachers in a lacking role ended up smoking. The chi-square test yielded a ρ-value of 0.000, indicating a significant relationship between the social environment, media/advertising exposure, the role of parents, the role of teachers, and smoking behavior. Conclusion: The study results demonstrate a significant influence of the social environment, media/advertising exposure, the role of parents, and the role of teachers on the smoking behavior of senior high school students.